WAVES OF INCREASE AND DECREASE IN THE WORLD OF ECONOMIC BUSINESS - Amirah Andika Rifdayanti; Safira Elfadhilah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In the world of economic business, there are waves of increases and decreases that can affect various aspects of a country's economy. Several factors influence this wave including government policies, global conditions, and technological changes. In global business dynamics, corporate wave ideas reflect a series of transformations, innovations and evolutions that cut across various industry sectors. The concept of corporate waves has become a representation of technological advances, social changes, and economic policies that induce significant changes in companies' business strategies and operational models. Corporate waves are often related to technological advances that open up new opportunities and change a company's operational methods. This wave reflects the pattern of change and transformation that occurs in companies amidst changes in markets, technology and consumer preferences. Corporate waves refer to the cyclical patterns of change that occur in the business world. In this context, companies go through phases of growth, stagnation, decline, and potential for revitalization or innovation. This research in-depth investigates the waves of increase and decrease in the world of economic business using a literature review approach. This research discusses the dynamics of modern business in analyzing the waves of increase and decrease in companies, company waves: transformation in the modern business world, and moving forward in the wave of global transformation.